2006
DOI: 10.2527/2006.841236x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets with cereal grains contaminated by graded levels of two Fusarium toxins on selected immunological and histological measurements in the spleen of gilts1,2

Abstract: Feeding experiments with diets containing Fusarium toxin-contaminated wheat were conducted to clarify the pathogenesis of immunological effects of Fusarium toxins to porcine spleen cells. Contaminated diets were fed to 36 Landrace prepubertal gilts for 35 d. Concentrations (as-fed basis) of the indicator toxins deoxynivalenol (DON) and zearalenone (ZON), respectively, were 210 and 4 (control--group I), 3,070 and 88 (group II), 6,100 and 235 (group III), and 9,570 and 358 microg/kg (group IV). No signs of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 41 publications
1
30
1
1
Order By: Relevance
“…The question why the DON release by the osmotic minipump was not as expected cannot be solved from the present results. However, the solubility and stability of DON in DMSO, water, PBS, and NaCl-solution under physiological conditions was proven several times in different cell cultures (Goyarts et al 2006a, b;Tiemann et al 2006Tiemann et al , 2008b. To the authors' knowledge, only one experiment (Prelusky 1997) has been conducted with pigs (10-13 kg bw, 6 weeks) implanted intraperitoneally with an osmotic pump (Alzet Model 1007D, 0.5 µL/h) filled with an aqueous solution of DON, resulting in an intraperitoneal DON dose of 2 µg DON/h (low dose, 48 µg/day, 3.7-4.8 µg/kg bw/day) and 5 µg DON/h (high dose, 120 µg/day, 9.2-12.0 µg/kg bw/day).…”
Section: Discussionmentioning
confidence: 99%
“…The question why the DON release by the osmotic minipump was not as expected cannot be solved from the present results. However, the solubility and stability of DON in DMSO, water, PBS, and NaCl-solution under physiological conditions was proven several times in different cell cultures (Goyarts et al 2006a, b;Tiemann et al 2006Tiemann et al , 2008b. To the authors' knowledge, only one experiment (Prelusky 1997) has been conducted with pigs (10-13 kg bw, 6 weeks) implanted intraperitoneally with an osmotic pump (Alzet Model 1007D, 0.5 µL/h) filled with an aqueous solution of DON, resulting in an intraperitoneal DON dose of 2 µg DON/h (low dose, 48 µg/day, 3.7-4.8 µg/kg bw/day) and 5 µg DON/h (high dose, 120 µg/day, 9.2-12.0 µg/kg bw/day).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo investigations provide information on the effects in whole animals, whereas cell specific answers result from in vitro investigations. For example, the summarized results reviewed by Tiemann et al (2006) about the toxicological data on the effects of ZEA and DON on different parameters relating to reproductive and non-reproductive organs in female pigs indicated that in vitro studies with porcine cell cultures only partially agree with that of in vivo experiments. An explanation could be the fact that sometimes the cells in vitro react more sensitively than those in vivo, because a direct interaction of chemical substances with the plasma membrane exists which may alter the membrane structure and function.…”
Section: In Vivo Studiesmentioning
confidence: 91%
“…Its species, which invade agriculturally important grains, are probably the most prevalent toxin-producing fungi of the northern temperate regions and are commonly found in cereals grown in America, Europe and Asia (Tiemann et al, 2006). Most members of the genus produce -under favorable environmental conditions -an array of secondary metabolites, which vary widely in chemical form.…”
Section: Fusarium Generamentioning
confidence: 99%
“…Immunoglobulins (IgA, IgG, and IgM) and complements (C3 and C4) concentrations were determined using an indirect enzyme-linked immunosorbent assay as described by Tiemann et al [13]. Briefly, plates were incubated at room temperature for 60 min and then washed five times in washing solution.…”
Section: Chemical Analysesmentioning
confidence: 99%